Congenital dermatofibrosarcoma protuberans in a seven-month-old infant initially misdiagnosed as infantile myofibroma: A case report - Chen-Jun Zheng; Chen-Liang Wan; Chuan-Bo Zhang; Bo Hai; Chun-Feng Huang (World Journal of Clinical Oncology, 2026)
BACKGROUND Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive cutaneous sarcoma predominantly observed in adults 30 years to 50 years of age. It is exceedingly rare in infants and is often misdiagnosed owing to its indolent growth and resemblance to benign lesions such as hemangiomas or fibromas. CASE SUMMARY A 7-month-old male infant presented with a congenital dorsal mass that had gradually enlarged since birth. Initial biopsy of the lesion resulted in a misdiagnosis of infantile myofibroma. Given the tumor’s progressive growth, wide local excision was performed with a 2-cm peripheral margin extending to the muscular fascia. Subsequent histopathological examination and immunohistochemical analysis (CD34+, SMA-, Desmin-, S-100-, HMB45-, and Ki-67 approximately 5%) confirmed the diagnosis of classic DFSP. Owing to resource constraints, testing for the COL1A1-PDGFB fusion gene was not performed. The patient experienced an uneventful recovery and underwent close follow-up. At the 2-year postoperative follow-up, clinical examination and ultrasonography revealed no evidence of local recurrence or metastasis. CONCLUSION At the 2-year follow-up, the patient exhibited no signs of disease recurrence. However, congenital DFSP requires prolonged surveillance beyond this period because of its potential for late local recurrence.